ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA PT MULTI BINTANG INDONESIA TBK - Chivalrind Ghanevi Ayuntari (Program Studi Manajemen, 2021)
This study aims to analyze the source and uses of working capital at PT Multi Bintang Indonesia Tbk and its effect on the company’s profitability. The source data of this study is financial statements of the company and financial statements of several companies from similar industries. The data taken from idx.co.id for period 2016-2020. The analysis was carried out by analyzing reports on sources and uses of working capital, analysis of working capital requirements and analysis of profitability ratios. After analyzing the results obtained that the company has managed working capital well even though the company had experienced a lack of capital for a certain period. In addition, the company can take advantage of the resources it has to make a profit.